2019
DOI: 10.29252/jhehp.5.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Neighbor Presence of Plant Growth-promoting Rhizobacteria (PGPR) and Arbuscular Mycorrhizal Fungi (AMF) Can Increase Sorghum Phytoremediation Efficiency in a Soil Treated with Pb Polluted Cow Manure

Abstract: accumulate in living organisms and plants [1]. These elements enter the environment mainly through anthropogenic sources, such as smelting processes, mining, fuel production, and industrial effluents [2]. Therefore, use of proper approached to the reduction of heavy metal availability is essential. Conventional remediation approaches for contaminated soils, sediments, and groundwater are based on the technologies that have been developed over the past two decades [3], including a wide variety of physical, chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The abundance of Cr in the soil indicates an environmental problem that is most likely originated from human activities, including chemicals used in agriculture, paint and leather industries, alloy production, and stainless steel [182,183]. It can be said that India's tanning industry alone imports between 2000 and In recent years, scientists have noted the positive effect of inoculating plants with AMF and adding earthworms, biochar, cow manure, lignin, and steel slag to increase uptake and stabilize Pb from contaminated environments [5,24,179,180]. They found that combining AMF with other factors improves phytoremediation in Pb-contaminated environments through increasing the uptake of nitrogen, phosphorus, potassium, and iron, reducing Pb transfer from root to shoot, increasing root colonization, improving soil pH, further plant growth, and increasing soil glomalin content [5,24,179,180].…”
Section: Chromium (Cr)mentioning
confidence: 99%
“…The abundance of Cr in the soil indicates an environmental problem that is most likely originated from human activities, including chemicals used in agriculture, paint and leather industries, alloy production, and stainless steel [182,183]. It can be said that India's tanning industry alone imports between 2000 and In recent years, scientists have noted the positive effect of inoculating plants with AMF and adding earthworms, biochar, cow manure, lignin, and steel slag to increase uptake and stabilize Pb from contaminated environments [5,24,179,180]. They found that combining AMF with other factors improves phytoremediation in Pb-contaminated environments through increasing the uptake of nitrogen, phosphorus, potassium, and iron, reducing Pb transfer from root to shoot, increasing root colonization, improving soil pH, further plant growth, and increasing soil glomalin content [5,24,179,180].…”
Section: Chromium (Cr)mentioning
confidence: 99%
“…Conventionally, bacterial species in the rhizosphere were isolated and identified using the traditional or culture-based method for isolating and classifying microorganisms. This method's main inadequacy is that it cannot identify the entire microorganism in a sample, making approximately 99% of the microorganism unknown [6]. Thus, only a few bacterial populations has been identified from the rhizosphere soils using conventional techniques, but not until the advent of next-generation sequencing techniques [33].…”
Section: The Rhizosphere Soil As a Treasure Trove For Bacterial Community Concentrationmentioning
confidence: 99%
“…In agro-based industry, plant root-associated bacteria have a beneficial effect on the growth and yield of crops and forest trees [5,6]. Plant growth-promoting rhizobacteria Agriculture 2021, 11, 75 2 of 18 (PGPB) are consortia of bacterial species that colonize the plant root region (rhizosphere), impacting plant growth and health advantageously.…”
Section: Introductionmentioning
confidence: 99%